ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN KEKURANGAN ENERGI KRONIK (KEK) MELALUI PEMBERIAN MAKANAN TAMBAHAN DI PUSKESMAS TANJUNG BALAI KARIMUN - Titin Sartini; Silvia Mona (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
World Health Organization describes the prevalence of Chronic Energy Deficiency in general in pregnancy, which is 35% to 75%. Indonesia's risk of developing CED is quite high, namely as much as 17.3% experienced by pregnant women with an age range of 15-49 years. The 2020 routine report data notes that of the 4,656,382 pregnant women who have LILA <23.5 cm, approximately 451,350 people are at risk of developing CED. Efforts made by the government in overcoming KEK are by providing Supplementary Food (PMT) to increase calorie and protein intake. The purpose of the study is to provide midwifery care for pregnant women in a comprehensive and sustainable manner for pregnant women with CED through the provision of additional food to meet the nutritional needs of pregnant women. The case report in this case study uses the case study method which consists of one mother which means one mother who is given pregnancy care using the SOAP method (Subjective, Objective, Analysis, Management). The study was conducted at the Tanjung Balai Karimun Health Center in January 2023. The subject used in this case study with midwifery care management was Mrs S, a pregnant woman with KEK. Data collection methods are participatory observation, interviews, measurements, documentation. The results of the study found that the mother was willing to consume PMT biscuits and maintain a good diet. Midwives can work together with nutrition officers in monitoring activities and then evaluating the provision of food and fulfillment of nutrition for pregnant women.